ТЕХНОЛОГІЯ РЕЦИКЛІЗАЦІЇ АКТИВНИХ МАТЕРІАЛІВ ЦИНК-МАРГАНЦЕВИХ ДЖЕРЕЛ СТРУМУ - Diamant, Viktor; Simonov, Andrey (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2021)
It is being investigated whether it is possible to develop a low-cost method for processing used Zn-MnO2 primary chemical power sources, which is focused on a closed cycle of generating zinc-manganese power sources from wasted batteries. It is proposed that chemical processing reagents be replaced with less dangerous ones for the environment and people, in accordance with «green chemi» principles. The existing hydrometallurgical method of processing of primary current sources with selective extraction of the spent part of the anode mass is modified and laboratory processed. The stage of additional extraction of arsenic is entered. The proposed technological scheme avoids heavy air loads in the form of carbon dioxide emissions by eliminating the stage of burning organic matter. The use of acetic acid allows to avoid sulfuric acid discharges and to obtain high-quality for secondary production of cathode mass of new chemical current sources, as well as to obtain technical zinc powder and active zinc powder using hydrometallurgical technology for anode mass production of primary batteries. Also, the presence of stages of extraction of heavy metal ions (Hg2 +, Pb2 +, Cd2 +) and Arsenic to obtain products that can be further used in other technological processes makes this technology virtually waste-free, and in the stages of recovery of acetic acid and hypochlorite – closed. Thus, the use of the proposed technological schemes allows to make such production not only a little harmful to the environment, but also for workers, as well as to simplify the requirements for technological equipment.